Environmental Flows to Estuaries and Coastal Lagoons Shape the Salinity Gradient and Generate Suitable Fish Habitat: Predictions From the Coorong, Australia - Brookes, Justin D.; Huang, Peisheng; Zhai, Sherry Y.; Gibbs, Matthew S.; Ye, Qifeng; Aldridge, Kane T.; Busch, Brendan; Hipsey, Matthew R. (Frontiers in Environmental Science, 2022)
Freshwater flows to estuaries shape habitat, transport nutrients to drive productivity, and generate a salinity gradient that impacts water quality and provides spawning cues for fish. The aim of this study was to quantify how environmental flows improved outcomes for a coastal lagoon system (the Coorong, South Australia), considering the export, and prevention of ingress, of salt from the system, and the increased available habitat for key fish biota. A hydrodynamic model was used to simulate salinity and water temperature, and to determine the salt exchange between the Coorong and ocean for the observed conditions with environmental water release included. Scenario simulations showed that maintaining river flow is shown to arrest salt intrusion from the ocean into the Coorong. Without environmental water, the net import of salt into the Coorong would have been considerably greater, ranging between 1.86 million tonnes in 2018–19 to approximately 2.33 million tonnes in 2019–20. The fresher conditions created by environmental water provision supported a considerable expansion of suitable fish habitat area, derived from a simple habitat index based on salinity and water temperature. Without environmental water the habitat suitable for mulloway would have contracted by 38% over the 3 year investigation period. A similar trend is evident for black bream, Tamar goby, greenback flounder, yelloweye mullet, congolli and smallmouth hardyhead. The results highlighted the importance of cumulative benefits from delivering environmental water over multiple years, with different results obtained if the environmental water provided regularly or just focused over a single year. The approach used in this work to relate hydrological changes from water management to indicators of habitat suitability through changes to physical attributes provides information to inform the evaluation of environmental watering, as well as a tool to support future decision making to maximise the benefits from this precious resource.